Plant succession on an active tundra mud slump, Garry Island, Mackenzie River Delta, Northwest Territories - Lambert, J. D. H. (Canadian Journal of Botany, 1976)
The vegetation in the latter stages of an active mud slump of known age on Garry Island, Mackenzie River Delta, N.W.T., is described using principal-component analysis. Three associations are recognized. Senecio congestus and isolated hummocks with dwarf shrub – heath vegetation dominate during the first 4 years after exposure. The Arctagrostis latifolia – Senecio congestus association that dominates after 4 years represents the second stage of development after the disappearance of recognizable hummocks. The Arctagrostis latifolia – Eriophorum scheuchzeri association that dominates after 6 years is the third stage in the revegetation sequence and represents further stabilization of the mud slump surface. The frequency of hummock-associated species is greatly reduced. The rapid rate of natural revegetation, in such a mud slump where the headwall had been receding, would suggest that man-induced reseeding programs, in all probability, would not speed up the process.